The Effect of Corporate Social Responsibility, Profitability, and Capital Structure on Firm Value in Coal Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange - Abdullah (Quantitative Economics and Management Studies, 2025)
Sustainable companies do not focus solely on economic activities but also integrate social and environmental dimensions. This study aims to examine the effect of corporate social responsibility (CSR), profitability, and capital structure zon firm value in companies in the coal mining sub-sector, both partially and simultaneously. A quantitative descriptive approach is employed, with data collected using a documentation technique. Firm value is proxied by price to book value (PBV); CSR is measured using economic, social, and environmental indicators based on GRI G4; profitability is proxied by return on investment (ROI); and capital structure is measured by the debt to equity ratio (DER). The results show that, partially, CSR and profitability have a significant effect on firm value, whereas capital structure does not. Furthermore, CSR, profitability, and capital structure jointly have a significant effect on firm value.